Conductive Composite Biosensor System for Electrochemical Indinavir Drug Detection - Natasha Ross; Nicolette Hendricks-Leukes; Rachel Fanelwa Ajayi; Priscilla Baker; Emmanuel I. Iwuoha (Journal of Chemistry)
Indinavir is a protease inhibitor antiretroviral (ARV) drug, which forms part of the highly active antiretroviral therapy during the treatment of HIV/AIDS. Indinavir undergoes first-pass metabolism through the cytochrome P450 (CYP) enzymes in the human liver, of which CYP3A4 is the most influential isoenzyme. Multidrug combination therapy and, as such, therapeutic drug monitoring (TDM) during HIV/AIDS treatment are therefore critical, to prevent adverse interactions. The conventional sensitive and specific assays available for quantifying ARV drugs, however, suffer from distinct disadvantages. In this regard, biosensors can be used to provide real time information on the metabolic profile of the drug. In this study, a biosensor with cobalt(III) sepulchrate trichloride {CoSep3+} as diffusional mediator was constructed. The biosensor platform consisted of CYP3A4 immobilized onto a gold nanoparticle (GNP) overoxidized polypyrrole (OvOxPpy) carrier matrix. The biosensor exhibited reversible electrochemistry, with formal potential determined as −624 ± 5 mV, from voltammetric analysis, with overall electron transfer being diffusion controlled. The biosensor showed typical electrocatalytic response to dioxygen (O2), exemplified by the distinct increase in the cathodic peak current (Ip,c). A concentration-dependent increase in Ip,c was observed in response to consecutive additions of Indinavir.